Wieloogniskowe soczewki wewnątrzgałkowe - Żelichowska, Beata; Rękas, Marek; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Multifocal intraocular lenses are the new option not only in cataract surgery, but either in refractive surgery. Use of multifocal lenses make patients less dependent on spectacle, than after implantation of monofocal intraocular lenses. In this article we present an actual review of multifocal intraocular lenses. Two main types of the implants: refractive and diffractive are described with their detailed characteristics. Special attention we paid on advantages and disadvantages as well as some limits to implantation of the multifocal implants.